PENGARUH PROGRAM FLASH SALE TERHADAP POLA PENGELUARAN KEUANGAN MAHASISWA DENGAN PERILAKU KONSUMTIF SEBAGAI VARIABEL MODERASI - Yuniar, Nadira Fianda; Nafiati, Lu'lu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025DO - 10.24843/EEB.2025.v14.i04.p12, 2025)
Flash sales is a marketing strategy frequently employed by e-commerce platforms, particularly Shopee. This strategy leverages the urgency of promotions to encourage consumer’s impulsive buying behavior. Such behavior can influence student’s financial spending patterns. The purpose of this study is to analyze the effect of flash sale programs on students' spending patterns, with consumptive behavior as a moderating variable. The respondents used in this study consisted of 101 students majoring in accounting in the Special Region of Yogyakarta who had made transactions through flash sale programs on the Shopee application. The respondents were selected using convenience sampling based on several predetermined criteria. Data were gathered through questionnaires with likert scale and using Google form. Data analysis technique using Moderated Regression Analysis (MRA) with SPSS software. The results of this study indicate s that flash sales gives a positive impact on student's financial spending patterns. Vice versa, impulsive buying behavior negatively moderates this relationship, thereby impulsive buying behavior actually weakens the effect of flash sale programs on student’s financial spending patterns